Conformation Analysis of Some 2,6-Diphenylthian-4-one Derivatives Using 1H and 13C NMR Spectral Data - Bhavani, N.; Asha, S. (Asian Journal of Chemistry, 2010)
Four new thian-4-one derivatives, viz., r-2,c-6-diphenylthian-4-one 1-oxide oxime (1), t-3-methyl-r-2,c-6- diphenylthian-4-one oxime (2), t-3-methyl-r-2,c-6-diphenylthian-4-one semicarbazone (3) and c-3-methyl-r-2,t-6-diphenylthian-4-one oxime (4) were synthesized and their 1H and 13C NMR spectra were recorded. In the light of the spectral data the conformations of these derivatives were derived. It has been found that compound (1) exists as an equilibrium mixture of chair form and boat form. In the boat form there is a possibility of intramolecular H-bonding between oxime hydrogen and S═O oxygen favouring it. Compounds (2) and (3) exist in chair form with —OH/—NHCONH2 group anti to the methyl group and compound (4) exists in non-chair form.